Konsep Berkah dalam Pandangan Ahlussunnah: Analisis Syarah Hadis tentang Tabarruk - Muhamad Rijal Zaelani (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The purpose of this study is to discuss the syarah on the hadith that allows tabarruk against pious people and their relics in the perspective of the Ahlussunnah. This research method uses a qualitative type through literature study using the analysis of syarah hadith. The results and discussion of this study include an explanation of the hadith syarah about tabarruk against pious people, objects and places that are considered to be able to bring down blessings from Allah SWT., and how the concept of blessing in the perspective of the Ahlussunnah. This study concludes that the concept of blessing in the view of Ahlussunnah can be done by expecting blessings through intermediaries such as pious people, objects and places that are glorified by Allah SWT which is in accordance with the hadith of the Prophet. This study recommends the importance of the concept of blessing for the Muslim community in the application of tabarruk in accordance with the hadith of the Prophet.